Clinical Predictors of the Need for Further Treatment Escalation in Patients with Type 2 Diabetes on Basal Insulin Therapy – A Retrospective Observational Study - Buchholz, Christina; Kahle-Stephan, Melanie; Meier, Juris J.; Nauck, Michael A. (Experimental and Clinical Endocrinology & Diabetes, 2019)
Background/Aims The aim of this study was to identify clinical characteristics that distinguish patients who achieve sufficient glycaemic control with basal insulin and oral glucose-lowering medications from those who need treatment intensification.Patients/Methods 213 out of 1 042 consecutively hospitalized type 2-diabetic patients were treated with basal insulin/oral agents. After titration to fasting glucose target, in 156 patients (73.2%) continuation of basal insulin treatment was recommended, while in 57 (26.8%), intensification of treatment was necessary. We compared patients’ characteristics and plasma glucose profiles between these groups.Results Patients needing intensified regimens (basal-bolus regimes, premixed insulin ;GLP-1 receptor agonists) had higher initial HbA1c values (87±17 mmol/mol [10.1±1.7%] vs. 80±19 mmol/mol [9.5±1.9%], p=0.028), were more likely to be female (49.1 vs. 25.0%, p=0.0014) and more obese, and required higher basal insulin doses (62±40 vs. 39±27 IU/d, p<0.0001). In both patient groups, basal insulin reduced fasting plasma glucose into the target range (6.6±1.3 vs. 5.7±0.8 mmol/l), however, in those needing treatment intensification, post-breakfast plasma glucose remained substantially higher after basal insulin titration (12.6±2.0 vs.9.4±1.6 mmol/l, p<0.0001). Before hospital discharge, similar plasma glucose profiles were reached in both groups.Conclusions Basal insulin therapy can provide satisfactory glucose control in more than 70% of patients with type 2 diabetes. Long diabetes duration, obesity, insulin resistance and female sex indicate a need for further treatment intensification.
Keywords: basal insulin; fasting plasma glucose; plasma glucose profiles; post-prandial plasma glucose; titration